Breast Cancer Advocacy and Public Policy - Frances M. Visco (Washington University Journal of Law & Policy, 2005)
The issue of breast cancer, and women’s health generally, is a political issue and requires an expanded approach to public interest law. Decisions that affect how individual women are treated—such as how much and what research is performed, whether the environmental connections to breast cancer are understood and dealt with, whether all women will have access to quality health care—are made at the political level. Appropriations for breast cancer research come from Congress. Congress tells the Food and Drug Administration (FDA) what to do, and the FDA approves drugs and devices. Government-regulated programs, such as Medicaid and Medicare, provide access to health care for many individuals in this country. Even private insurance companies are regulated by the states. As a lawyer, I recognize that to have a significant impact on breast cancer—not just for individual women but on the systems that affect all women—the usual public interest law approach is not enough. Necessary, overarching change will not likely come about through the judicial system, a system that is bound by tradition and precedent. What breast cancer advocates realized in the early 1990s was the need to make new law to change the systems that affect everyone— the systems of research, access to care and regulation. Fortunately, my background and education equipped me to meet the challenges of forging new law and refusing to settle for the status quo in the name of precedent.
Keywords: Breast – Cancer; Breast cancer; Government policy; Citizen suits (Civil procedure)